A practical-theological reflection on the usage of symbols and metaphors in intercultural pastoral care in South Africa - Plessis, Amanda Du (HTS teologiese studies, 2016)
The African continent is associated with a variety of problems. Irrespective of having achieved a new democracy more than two decades ago, South Africa still seems to suffer the same fate as the rest of the continent because of the inability to solve its innate challenges. However, at grass roots level South Africans are desperately seeking ways of moving away from this problem-focused paradigm to a more constructive and assertive paradigm where South Africans can truly be reconciled as a ‘rainbow nation’ despite the different cultures. Scholars who have written about this intercultural challenge are of the opinion that intercultural hermeneutics no longer works with a split between Christ and culture, but rather with the interconnectedness between Christ and culture, without the sacrifice of the culture’s uniqueness. One cannot understand religion, faith and spirituality without understanding culture. This article investigates the church’s responsibility to provide pastoral care to the people of South Africa within an intercultural paradigm by using different symbols and metaphors. The research question concentrates on the interconnectedness of the Christian faith and the different cultures in South Africa. It examines how a pastoral approach, using symbols and metaphors, could contribute to the avoidance of the mere ‘Christianisation’ of the culture, resulting in an approach where Christ is the authentic transformer of culture.